Interoperable server-based cache consistency algorithm - Bodorik, P.; Jutla, D.; Yueping Lu (Proceedings. International Database Engineering and Applications Symposium, 2004. IDEAS '04, 2004)
Numerous caching algorithms have been investigated for the client-server object database management systems. The algorithms not only ensure cache consistency by preventing applications' access to stale data, but they also support transactional properties. Caching algorithms have been classified in a number of ways - one classification is into avoidance and detection categories, depending on whether access to the stale data is avoided, usually by locking, or permitted and then any conflict detected at commit time. Detection-based algorithms have better performance but can lead to high abort rate that is unacceptable for interactive applications. It is for this reason that avoidance-based algorithms are usually adopted in practice. This work describes a server-based interoperable transactional caching algorithm that concurrently supports the leading avoidance-based (adaptive callback locking (ACBL)) and detection-based (adaptive optimistic concurrency control (AOCC)) algorithms. At a client either the avoidance or the detection caching algorithm is used without any changes. It is the server-side caching algorithm that concurrently supports both avoidance and detection client-side caching.